Penguatan Life Skill Santri Melalui Program Keputrian di Pesantren - Kamilatun Niyah; Irfan Musdat (Chalim Journal of Teaching and Learning (CJoTL), 2021)
This research is motivated by the importance of fostering, empowering, and strengthening life skills in Islamic boarding schools in the fields of skills and technology, as well as the importance of the concepts and assumptions that underlie the Islamic education system. In this study, it will be explained how to strengthen the life skills of students at the Babussalam Paelaran female Islamic boarding school. The focus of this research is: (1) How is the implementation of the girlhood program at the Babussalam Women's Islamic Boarding School in improving the life skills of students, (2) What are the supporting and inhibiting factors for strengthening the life skills of students through the girlhood program at the Babussalam Women's Islamic Boarding School. The type of research used is a qualitative descriptive method, with an ethnographic research type. The data analysis technique uses qualitative descriptive data analysis techniques with steps: data collection, data reduction, data presentation, drawing conclusions or verification. The results of this study indicate that the girlhood program at the female Babussalam Islamic boarding school performances provides life skills to students including personal skills, social skills, and academic skills. Strengthened through syi'ar activities on online-based social media and empowering that knowledge when they have become alumni. There are supporting and inhibiting factors of the girlhood program at the Babussalam Islamic boarding school, including those related to the talents and interests of the students, the availability of facilities and the background of the students.